THE IMPACT OF THE CREDIT CAPACITY OF BANKS IN ACHIEVING ADDED ECONOMIC VALUE: A SAMPLE OF PRIVATE COMMERCIAL BANKS LISTED IN THE IRAQ STOCK EXCHANGE - Ameer Ali Ghazi; Safwan Eldanaoui (Galaxy International Interdisciplinary Research Journal, 2023)
Credit in banks is considered one of the basic functions of the work of banks, and the possession of banks of sufficient credit capacity can contribute to the improvement of banking activity. Therefore, our study entitled / The impact of the credit capacity of banks in achieving added economic value (a sample of private commercial banks listed in the Iraq Stock Exchange) / With the aim of diagnosing the level of application of bank credits and analyzing their theoretical and practical relationship to private commercial banks, while drawing theoretical and practical conclusions based on two theoretical frameworks and a practical analysis of the problems and hypotheses of the study. And to identify the concept of credit capacity and added economic value in private Iraqi commercial banks, with a diagnosis of the reality of indicators of credit capacity in private commercial banks, in addition to measuring and determining the impact of credit capacity in private commercial banks in achieving added economic value, and to identify the achievement of economic added value for commercial banks. Iraqi Special